Development of an empirical relation to assess soil spatial variability for off-road trafficability using terrain similarity analysis & geospatial data. Issue 3 (4th March 2021) - Pundir, Sunil Kumar; Garg, Rahul Dev
ABSTRACT: Soils trafficability is measure of soil strength required to support the manoeuvring of military vehicles. Trafficability can be measured with the tests performed using cone penetrometer and moisture metre to understand the complexity of phenomenon. Empirical relation can be developed through the outcomes of these tests. This empirical relation can be used in tandem with geospatial data to understand the heterogeneous soil behaviour and its impact on trafficability. Further, it will enhance the remote sensing data capability to assess the trafficability in inaccessible areas. In this study, a numerical approach is described in which geo-parameters like land use, soil, elevation and moisture are quantified using various data sources such as remote sensing and ground survey information. Terrain similarity analysis was performed to find analogous soil patches of homogenous nature. The aim of this paper is to outline a procedure, which will be useful for off-road trafficability studies. The current advancement in remote sensing technologies and ground survey from digital equipment was used to have better accuracy of results along with better understanding of utilization of geo-spatial data. It will pave the way to analyse the terrain suitability for off-road trafficability operation.